LANGUAGE IDEOLOGY IN BRAZILIAN INDIGENOUS ACADEMIC PRODUCTION - Bollettin, Paride; Côrtes Servelati, Fabrício (Revista de Letras Norte@mentos, 2025)
This work maps academic discussions proposed by indigenous researchers within a broader context in which the presence of people from diverse ethnicities and cultural backgrounds in Brazilian universities have challenged the hegemonic status of Eurocentric concepts and methods of knowledge production. Specifically, we seek to identify which language ideologies – understood as beliefs about language use and structure (Silverstein, 1979) – they mobilize in their discourses and meta-discourses. Our corpus comprises fifteen texts authored by self-declared Indigenous researchers (including articles, undergraduate theses and master’s dissertations) in Linguistics and related fields in the Social Sciences. From this material, we found three major recurring themes: (1) the principles guiding academic education for indigenous teachers; (2) efforts towards the preservation and/or revitalization of Indigenous languages; (3) the challenges faced by Indigenous students and scholars within the university setting. The results indicate that indigenous researchers have been expanding the boundaries of academic orthodoxies, particularly with respect to research methodologies and reporting strategies. In their work, language is approached not as an abstract system, but as inextricably linked to knowledge, history, and other social practices. Nevertheless, essentialist notions of language are at times strategically employed in order to facilitate intelligibility and to emphasize cultural distinctiveness.